Brontorina - Howe, James, 1946-; Cecil, Randy (Somerville, Massachusetts : Candlewick Press, 2013)
Despite her size and not having the proper footwear, a determined dinosaur pursues her dream of becoming a ballerina.
Ages 4-8.
390
Accelerated Reader
Keywords: Dinosaurs -- Juvenile fiction; Ballet dancing -- Juvenile fiction; Body size -- Juvenile fiction; Dinosaurs -- Fiction; Ballet dancing -- Fiction; Ballet dancing; Body size; Dinosaurs; Dinosaurs -- Fiction; Ballet dancing -- Fiction; Size -- Fiction; Dinosaurs; Fiction; Juvenile works